Syk-MyD88 Axis Is a Critical Determinant of Inflammatory-Response in Activated Macrophages - Yi, Young-Su; Kim, Han Gyung; Kim, Ji Hye; Yang, Woo Seok; Kim, Eunji; Jeong, Deok; Park, Jae Gwang; Aziz, Nur; Kim, Suk; Parameswaran, Narayanan; Cho, Jae Youl (Frontiers in Immunology, 2021)
Background: Inflammation, a vital immune response to infection and injury, is mediated by macrophage activation. While spleen tyrosine kinase (Syk) and myeloid differentiation primary response 88 (MyD88) are reportedly involved in inflammatory responses in macrophages, their roles and underlying mechanisms are largely unknown. Methods: Here, the role of the MyD88-Syk axis and the mechanism by which Syk and MyD88 cooperate during macrophage-mediated inflammatory responses are explored using knockout conditions of these proteins and mutation strategy as well as flowcytometric and immunoblotting analyses. Results: Syk rapidly activates the nuclear factor-kappa B (NF-B) signaling pathway in lipopolysaccharide (LPS)-stimulated RAW264.7 cells, and the activation of the NF-B signaling pathway is abolished in Syk−/− RAW264.7 cells. MyD88 activates Syk and Syk-induced activation of NF-B signaling pathway in LPS-stimulated RAW264.7 cells but Syk-induced inflammatory responses are significantly inhibited in MyD88−/− RAW264.7 cells. MyD88 interacts with Syk through the tyrosine 58 residue (Y58) in the hemi-immunoreceptor tyrosine-based activation motif (ITAM) of MyD88, leading to Syk activation and Syk-induced activation of the NF-B signaling pathway. Src activates MyD88 by phosphorylation at Y58 via the Src kinase domain. In addition, Ras-related C3 botulinum toxin substrate 1 (Rac1) activation and Rac1-induced formation of filamentous actin (F actin) activate Src in LPS-stimulated RAW264.7 cells. Conclusions: These results suggest that the MyD88-Syk axis is a critical player in macrophage-mediated inflammatory responses, and its function is promoted by an upstream Src kinase activated by Rac1-generated filamentous actin (F-actin).